Frequency hopping using CDMA to avoid malicious attack in han networks - Ridha, Hussein Ali (2020)
Frequency hopping and Code-Division Multiple Access (CDMA) is often deployed to protect wireless communication from malicious attacks. The data is enabled to be received by the recipients. The data is delayed or blocked when it try to enter the network. This project is developed by hybrid the Frequency Hopping with CDMA in a tangible way to protect the data by giving them an automatic protection. The results have been proved that by hybrid the Frequency Hopping and CDMA shows a better performance in protecting the data compared to the system that just using Frequency Hopping or CDMA only. It has been proved by simulation results that nodes protected by using CDMA and Frequency Hopping will give a better protection with the death nodes will only appears if the nodes are more than 150.